Характеристики особистісного профілю чинних військовослужбовців із диссомнічними проявами - Гук, Г. В.; Guk, G. V. (Запорізький державний медичний університет, 2023)
Мета роботи – шляхом вивчення особистісного профілю дослідити особливості психопатогенезу та вплив особистісних характеристик на патопсихологічне наповнення диссомнічних проявів у чинних військовослужбовців Збройних сил України (ЗСУ). Матеріали та методи. У проспективне клінічне дослідження на базі Військового госпіталю в/ч 3309 (м. Запоріжжя) залучили 64 чинних військовослужбовців ЗСУ з неорганічними порушеннями сну, які сформували групу дослідження. У групу порівняння залучили 40 пацієнтів, які перебували на лікуванні в відділенні межових станів КНП «Обласний клінічний заклад з надання психіатричної допомоги» Запорізької обласної ради та мали порушення сну в рамках невротичних психічних розладів. Під час дослідження застосували анамнестичний, клініко-психопатологічний, психодіагностичний, клініко-психофеноменологічний і клініко-статистичний методи. Як психодіагностичний інструмент обрали опитувальник акцентуацій характеру та темпераменту Леонгарда–Шмішека. Aim: to study specifics of psychopathogenesis and the influence of personal characteristics on the pathopsychological content of dissomnic manifestations in active servicemen of the Armed Forces of Ukraine by examining the personal profile. Materials and methods. In total, 64 active servicemen of the Armed Forces of Ukraine with inorganic sleep disorders were included in a prospective clinical study on the basis of Military Hospital of Military Unit 3309 (Zaporizhzhia) and served as the study group; the comparison group included 40 patients who were treated at the Department of Borderline Conditions of “Regional Clinical Institution for the Provision of Psychiatric Care” of Zaporizhzhia Regional Council and had sleep disorders within neurotic mental disorders. To achieve the aim of the study, anamnestic, clinical-psychopathological, psychodiagnostic, clinical-psychophenomenological and clinical-statistical methods were used. As a psychodiagnostic tool, the Methodology for studying personality accentuations of K. Leonhard and G. Shmishek was chosen. Results. The most common types of accentuation in active servicemen with dyssomnic manifestations were sticking (18.75 % of the contingent), dysthymic (17.19 %) and hyperthymic (9.38 %). The most frequent combined clinical types of accentuations were “dysthymic-sticking” (9.38 %), “anxious-dysthymic” (4.69 %) and “hyperthymic-demonstrative” (3.13 %).
Characteristics of the personal profile of active servicemen with dissomnic manifestations
ORCID ID: 0000-0003-2218-3314
Keywords: розлади сну; військовослужбовці; учасники бойових дій; психічні розлади; психогенні розлади; клініка; особистість; психічне здоров’я; dyssomnias; military; combatants; mental disorders; psychogenic disorders; clinic; personality; mental health